Penggunaan Student Centered learning dalam Pengajaran dan Pembelajaran di Jabatan Kejuruteraan Awam, Politeknik Sultan Mizan Zainal Abidin - Azreen Harina Binti Azman; Hassan Bin Ismail (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2023)
SCL is one of teaching and learning's methods in Outcome Based Education (OBE). This action research was conducted to identify the implementation stage of SCL in teaching and learning at JKA, PSMZA. Respondents involved are 44 lecturers of JKA, PSMZA. The objectives of this study are to identify the known SCL methods, the use of SCL and the teaching skills among lecturers at JKA, PSMZA. The methods used are quantitative and qualitative research methods. A set of questionnaire was developed and distributed to a sample of the lecturers at JKA, PSMZA. The findings show that 55% of the respondents are less skilled about the SCL method in teaching and learning. While 48% of respondents did not master the Problem Based Learning (PBL) method. Three proposed action plans have been proposed for improvement in JKA, PSMZA to make teaching and learning more attractive and active in line with SCL's implementation efforts. The execution of the action is completed within 2 months. The action plan is to ensure e-learning with a learning system application is blended using the CIDOS platform, organizing SCL courses, seminars and workshops as well as promoting and promoting the use of TECC rooms. After the implementation of the action, the SCL method of constructing the questionnaire known by the lecturer showed an increase of 12%. For the construct of SCL use in teaching and learning by lecturers, C2 items using different teaching methods in teaching and learning increased by 13% from 77% to 90% and second observation increased the use of SCL in teaching and learning by lecturers getting a score of 13.7 is increased 5.4. In conclusion, SCL in teaching and learning at JKA, PSMZA is at a satisfactory level and can still be improved from time to time.